2021
DOI: 10.1111/jocn.16032
|View full text |Cite
|
Sign up to set email alerts
|

United States nurses' experiences during the COVID‐19 pandemic: A grounded theory

Abstract: Objective The objective of this study was to explore nurses' experiences and perceptions at selected United States (U.S.) healthcare sites during the COVID‐19 pandemic. Background The COVID‐19 pandemic brought rapid changes to the healthcare community. While a few studies have examined the early pandemic experiences of nurses in China and Europe, nurses' experiences across the United States have remained relatively underexplored. Design A qualitative study design was used. Methods Using a constructivist ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
124
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(142 citation statements)
references
References 47 publications
12
124
0
6
Order By: Relevance
“…This study found that the COVID-19 pandemic has been a stressful period for nurses and HCAs in general practice, aligning with international accounts of primary care25 27 29 35–37 39 56–58 and nurses’ experiences in general 26 28 30–34 40 59–62. The necessity for meaningful and accessible short-term and long-term mental health support and continuous education and training are key recommendations in the literature 21–23 25 28 31 32 37 38 40 57 59.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…This study found that the COVID-19 pandemic has been a stressful period for nurses and HCAs in general practice, aligning with international accounts of primary care25 27 29 35–37 39 56–58 and nurses’ experiences in general 26 28 30–34 40 59–62. The necessity for meaningful and accessible short-term and long-term mental health support and continuous education and training are key recommendations in the literature 21–23 25 28 31 32 37 38 40 57 59.…”
Section: Discussionsupporting
confidence: 53%
“…Interviews were directed by a topic guide (box 1), ensuring important topics were covered while allowing exploration of novel ideas. The initial topic guide was based on the themes from existing literature 25–40. Clarity and focus of some questions were adjusted following a pilot interview with a practice nurse; the pilot interview was therefore not included in data analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…International researchers reported that nurses dealt with and attempted to overcome their challenges and feelings and emotional responses by coping during the pandemic. Nurses in the United States [ 17 ] and India [ 45 ] used teamwork and peer support, and used personal coping strategies, such as relationship development, play, exercise, meditation, and distractions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the nursing experience of patients with COVID-19 are underway in countries in various trajectories of the COVID-19 pandemic, such as Spain [ 14 ], Italy [ 15 ], Canada [ 16 ], the United States [ 17 ], and China [ 18 ], and these previous studies are focused on the lived nursing experience itself or the ethical aspect. Experiences of nursing care reported so far are summarized as providing nursing care [ 14 , 15 , 16 ], psychosocial and emotional aspects [ 14 , 15 , 18 , 19 ], resource management [ 14 , 16 ], struggling on the frontline [ 19 , 20 ], personal growth [ 18 , 19 ] and adapting to changes [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%